Pengaruh Dana Pihak Ketiga, Financing to Deposit Ratio dan Non Performing Finacing Terhadap Pembiayaan Murabahah Pada Bank Umum Syariah di Indonesia Tahun 2018-2022 - Wawan Hendriawan; Erwin Saputra Siregar; Nurfitri Martaliah (Jurnal Kajian dan Penalaran Ilmu Manajemen, 2024)
Financing is one type of sharia banking activity which is meant by financing is the provision of funds or bills which are equivalent to profit sharing transactions in the form of mudharabah and musyarakah, rental transactions in the form of ijarah or hire purchase in the form of ijarah, mutaniya bittamlik, sale and purchase transactions in in the form of murabhahah, salam and istisna receivables, lending and borrowing transactions in the form of qards and service rental transactions in the form of ijarah for multi-service transactions. This research aims to determine the influence of DPK, FDR and NPF on murabahah financing in Islamic commercial banks for the 2018-2022 period. This type of quantitative research, the data used is secondary data taken from the OJK website. This research uses the multiple linear regression method. The research results show that the variables third party funds (DPK), financing to deposit ratio (FDR) and non-performing financing (NPF) simultaneously have a significant influence on murabahah financing in Islamic commercial banks for the 2018 - 2022 period.